PENDAMPINGAN PEMBUATAN NOMER INDUK BERUSAHA MELALUI OSS DAN ANALISIS SWOT UNTUK 7 UMKM DI YOGYAKARTA - Adik Isma Aryani Choiriyah; Annya Anugrahaning Salbiah; Sri Ekanti Sabardini (Bajang Institute, 2023)
The number of Indonesian entrepreneurs until 2023 who have a new NIB is around 2.500.000. One of the lecture materials in SMEs and Cooperatives in STIM YKPN requires students to accompany MSMEs to register NIB. The activity began with making an email for MSMEs, the registration process guided by a Speaker from GARDA, and printing NIB to be submitted to MSMEs.Students groupMMSMEs. Analysis 10 MSMEs managed to get NIB and SWOT analysis